Turning Point or Illusion of Causality? Implications of Russian Aggression Against Ukraine for Building the Security of the European Union (Economic and Political Thought, 2023)
The purpose of this article is to discuss the future of the European project in the context of building a coherent and effective security model, as well as to provide insight into the peculiar cognitive dissonance that occurred in the EU after realising the consequencesof Russian aggression against Ukraine for European security. Recognising the Russian aggression against Ukraine as a point on a continuum of ontological uncertainty, the author wonders whether this event led to a breakthrough in the strategic programming of European security, or rather demonstrated the illusion of causality and communitarianism in the EU. Both reactive and proactive actions of the EU in the area of security in 2016–2023 were analysed and evaluated. In particular, attention was paid to the constructivist reading of the sense of urgency or immediacy of change, which is conveyed by the language of EU documents expressing the grouping’s determination to increase capabilities, the will to act, strengthen resilience and ensure solidarity and mutual assistance among member states.
Keywords: European Union, Ukraine, security, multilateralism, pragmatism, turning point, strategic compass